2001
DOI: 10.3354/meps211235
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acids as indicators of nutritional condition in the Norway lobster Nephrops norvegicus

Abstract: Changes in nucleic acid concentration of the gill, hepatopancreas and abdominal muscle tissue of the Norway lobster Nephrops norvegicus (L.) were examined after 6 and 12 wk of starvation. Significant decreases in RNA concentration, RNA:protein ratio and RNA:DNA ratio were recorded in abdominal muscle tissue following starvation, but not in gill or hepatopancreas tissue. Samples of abdominal muscle tissue were taken from lobsters from 2 sites in the Clyde Sea area, Scotland. These were south of Ailsa Craig, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…4). These findings agree with earlier studies that have shown RNA concentration per biomass unit to be a more sensitive indicator of nutritional condition than RNA:DNA ratios in lobsters (Parslow-Williams et al 2001), shrimps (Moss 1994a, and fish (Ferguson & Danzmann 1990). One of the criticisms of using RNA-based indices as measures of growth rate has been that they may appear to correlate with growth rates purely as a function of ontogenetic change.…”
Section: Discussionsupporting
confidence: 74%
“…4). These findings agree with earlier studies that have shown RNA concentration per biomass unit to be a more sensitive indicator of nutritional condition than RNA:DNA ratios in lobsters (Parslow-Williams et al 2001), shrimps (Moss 1994a, and fish (Ferguson & Danzmann 1990). One of the criticisms of using RNA-based indices as measures of growth rate has been that they may appear to correlate with growth rates purely as a function of ontogenetic change.…”
Section: Discussionsupporting
confidence: 74%
“…Otherwise, the RNA/DNA ratio can be used as a relative value in order to detect changes over time or analyse differences between groups (Vrede et al 2002;Olsson et al 2008). RNA/DNA ratios range from 1 to 5 in marine fish larvae (Buckley 1984;Clemmesen et al 1997) and from 0.5 to 8 in marine benthic crustaceans (Parslow-Williams et al 2001;Desai and Anil 2002) and up to 15 in zooplankton (Vrede et al 2002).…”
Section: Gammarus Fossarummentioning
confidence: 99%
“…Similarly, a strong positive relationship between nucleic acid ratios (i.e. short-term growth rate) and food availability has been found in bivalves (Wright & Hetzel 1985, Dahlhoff & Menge 1996, crustaceans (Wagner et al 1998, Parslow-Williams et al 2001) and juvenile and larval fish (Buckley et al 1999). Yet these studies did not contrast negative and positive effects of stressors like in the present laboratory experiments.…”
Section: Food Availability and Hypoxiamentioning
confidence: 99%